MANAJEMEN SDM DALAM PENINGKATAN NILAI PENDIDIKAN ISLAM DAN PENDIDIKAN KARAKTER SANTRIWAN - Hamsaturrahman; Muhammad; Yudin Citriadin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Human Resource Management (HRM) is a series of processes involving planning, organizing, mobilizing, and evaluating in an effort to empower all potential within educational institutions, particularly Islamic boarding schools. This study aims to reveal how the HRM process determines the effectiveness of Islamic education and the character building of students at the Mu'allimin Muhammadiyah Narmada Lombok Bara Islamic Boarding School. This study uses a qualitative approach with a case study method. Data collection techniques were carried out through unstructured interviews, non-participatory observation, and documentation. Research informants included the Mudir, Wadir, Principal, Teachers, and Students. The results showed that the implementation of HR management on improving Islamic education values was seen through the strengthening of subjects such as Aqidah, Akhlak, Hadith, and Fiqh. Meanwhile, the influence on character education is carried out through efforts to emphasize values such as discipline, responsibility, honesty, and religious attitudes. Thus, HR management plays an important role in improving the quality of education and shaping the character of students holistically.